Anthropometric and physiological differences between first team and reserve soccer players aged 10-14 years at the beginning and end of the season - Gravina, L.; Gil, S. M.; Ruiz, F.; Zubero, J.; Gil, J.; Irazusta, J. (The Journal of Strength and Conditioning Research, 2008)
The aim of this article was to identify differences in the anthropometric and physiological characteristics of first team and reserve young soccer players (10-14 years old) at both the beginning and end of the soccer season. Body composition was calculated by measuring weight, height, skinfold, limb circumference, and joint diameter. VO2max was estimated by Astrand's test. Sprint and jump tests were also performed. In general, first team players (FTPs) were taller and leaner. However, the most relevant difference that we found at the beginning of the season was that FTPs had shorter sprint times than reserves in the 30-m test (both flat and with 10 cones). Moreover, these differences in sprint time were more marked at the end of the season. In addition, jump test performance by the reserves declined from the beginning to the end of the season. These results indicate that sprint time is an important factor associated with selection as an FTP between the ages of 10 and 14 years. The progression of the FTPs during the course of the season is better than that of the reserves and is associated with a different degree of growth and maturity. These findings should be taken into account by trainers and coaches to avoid a bias against late maturing or younger soccer players.